1979
DOI: 10.1111/j.1365-2559.1979.tb03014.x
|View full text |Cite
|
Sign up to set email alerts
|

The trachea in children with tracheo‐oesophageal fistula

Abstract: Forty tracheas from children with tracheo-oesophageal fistulae were histologically analysed for structural deformity. Thirty (75%) had a deficiency of cartilage; 24 (60%) showed an increase in the length of the transverse muscle, and 26 (65%) had a longer than average internal perimeter. Only six tracheas were entirely normal. The position of the fistula bore little relationship to the abnormalities found. Since in only nine patients were abnormalities restricted to the site of the fistula, we believe that car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
9

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(66 citation statements)
references
References 14 publications
1
56
0
9
Order By: Relevance
“…In the adriamycin-induced rat model, the trachea develops directly from the upper foregut rather than as a separate bud or anterior extension of the foregut. The high incidence of tracheomalacia found in this model (unpublished results) and in humans (Wailoo and Emery, 1979) may be secondary to the fact that the tracheal primordium is abnormal. Certainly, we observed that at day 12 the upper foregut appeared histologically more like primitive esophagus than normal trachea in that it had simple columnar epithelium.…”
Section: Discussionmentioning
confidence: 58%
“…In the adriamycin-induced rat model, the trachea develops directly from the upper foregut rather than as a separate bud or anterior extension of the foregut. The high incidence of tracheomalacia found in this model (unpublished results) and in humans (Wailoo and Emery, 1979) may be secondary to the fact that the tracheal primordium is abnormal. Certainly, we observed that at day 12 the upper foregut appeared histologically more like primitive esophagus than normal trachea in that it had simple columnar epithelium.…”
Section: Discussionmentioning
confidence: 58%
“…Its pathogenesis is also conjectural, despite careful histopathological 13,14 and endoscopic 11 studies. TM is easily categorized as primary when no other lesions exist outside the trachea.…”
Section: Discussionmentioning
confidence: 99%
“…3 Subsequent studies on this subject also support the concept of TM in esophageal atresia being a primary abnormality. 13,2,14 Its significance on the management of EA is obvious, as 16%-20% of children suffer from symptomatic tracheomalacia, which together with gastroesophageal reflux is an important cause of late morbidity. 16 Our own finding of two patients with esophageal atresia and TM, out of a total of approximately 40 EA treated in the period, is probably an underrepresentation.…”
Section: Discussionmentioning
confidence: 99%
“…Wailoo and Emery [5] noted a spectrum of tracheomalacia in an autopsy study of 40 children, involving the whole length in 10%, half of the trachea in 47%, and the short segment of the fistula in 22%. A lengthening of the membranous muscle went along with a shortening of cartilage length.…”
Section: Commentmentioning
confidence: 99%